Brief Guide to Agatha Christie - Cawthorne, Nigel (London Constable & Robinson Ltd., 2014)
Agatha Christie's 80 novels and short story collections have sold over two-billion copies in more than 45 languages, more than any other author. This Brief Guide explores Christie's life and work from her first novel, The Mysterious Affair at the Styles, to her last, Sleeping Murder.
Keywords: The Life and Times of The Queen of Crime